Hidden Curriculum in Islamic Religious Education: Production of Values and Social Piety in Islamic Schools - Mohammad Muchlis Solichin; Mohammmad Hasan; Nor Hasan; Siswanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Palangkaraya, 2026)
This study examines the hidden curriculum in Islamic Religious Education (PAI/IRE) in Islamic schools and its contribution to value production and the formation of students' social piety. Employing a qualitative approach with a multiple case study design, the research was conducted in three Islamic Senior High Schools in East Java, Indonesia, over ten months. Data were collected through participant observation, in-depth interviews with IRE teachers, school principals, students, and parents, and documentary analysis. Findings reveal that the hidden curriculum operates through three primary channels: classroom climate and daily ritual routines, relational expectations between teachers and students, and the symbolic dimensions of the school's physical space. These channels collectively produce value dispositions — honesty, social care, collective responsibility, and empathy — that extend substantially beyond formal learning outcomes. This article argues that social piety, understood as a religious orientation expressed through ethical and just social action, is the primary product of an effective IRE hidden curriculum. Theoretical and practical implications for IRE curriculum development and Islamic educational policy are critically discussed.